2021
DOI: 10.3390/ijerph18094664
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Approach to Study the Effects of Realistic Environmental Mixture of Linuron and Propamocarb on Zebrafish Synaptogenesis

Abstract: The reasons behind the extensive use of pesticides include the need to destroy vector organisms and promote agricultural production in order to sustain population growth. Exposure to pesticides is principally occupational, even if their persistence in soil, surface water and food brings the risk closer to the general population, hence the demand for risk assessment, since these compounds exist not only as individual chemicals but also in form of mixtures. In light of this, zebrafish represents a suitable model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…Synaptogenesis occurs throughout an organism’s life cycle, and the period of explosive synaptic density appears early during brain development at the larval stage. , Synaptogenesis is the final step in the development of the CNS, leading to the establishment of a neural network . Previous studies have reported that the synaptogenesis process in zebrafish and mice was affected by different organic environmental contaminants, such as pesticides, bisphenol A, and organophosphate flame retardant triphenyl phosphate, thus inducing neurotoxicity. In the present study, the synaptogenesis signaling pathway was predicted to be the most inhibited canonical pathway, suggesting a disruption of synapse formation following PFNA exposure. Comprising an important part of the synaptogenesis signaling pathway (Figure B), CREB signaling in neurons was also predicted to be significantly inhibited by PFNA, potentially disrupting proper synaptogenesis .…”
Section: Discussionmentioning
confidence: 70%
“…Synaptogenesis occurs throughout an organism’s life cycle, and the period of explosive synaptic density appears early during brain development at the larval stage. , Synaptogenesis is the final step in the development of the CNS, leading to the establishment of a neural network . Previous studies have reported that the synaptogenesis process in zebrafish and mice was affected by different organic environmental contaminants, such as pesticides, bisphenol A, and organophosphate flame retardant triphenyl phosphate, thus inducing neurotoxicity. In the present study, the synaptogenesis signaling pathway was predicted to be the most inhibited canonical pathway, suggesting a disruption of synapse formation following PFNA exposure. Comprising an important part of the synaptogenesis signaling pathway (Figure B), CREB signaling in neurons was also predicted to be significantly inhibited by PFNA, potentially disrupting proper synaptogenesis .…”
Section: Discussionmentioning
confidence: 70%
“…Many studies were conducted to test the innocuity of additives and preservatives, such as sodium benzoate [ 157 ], methylparaben [ 158 ], or nitrite [ 159 ]. However, the most interesting investigations refer to the effects of agrochemicals, which include pesticides [ 160 ] and herbicides [ 161 ], pharmaceutical residues, or heavy metals. Additionally, through zebrafish models, the correlation between certain pollutants and the PD-like phenotype has been reported even more.…”
Section: Models To Study the Role Of Nutrition In Parkinson’s Diseasementioning
confidence: 99%
“…With the continuous development of the global economy and the growth of population, fungicides have played an imperative role in protecting plants to ensure food quality and safety. , Among all fungicides, succinate dehydrogenase inhibitors (SDHIs), one of the best-selling categories, have attracted a lot of attention from pesticide chemists due to their excellent and broad-spectrum antifungal activities in recent years. From 1996 to 2022, there are 24 SDHIs in the market, in which pyrazole-4-carboxamides take the largest proportion (12:24) (Figure A) . However, the overuse of SDHIs over several decades has resulted in the development of resistance in fungi. The Fungicide Resistance Action Committee (FRAC) has listed SDHIs as medium to high resistance risk fungicides. , Therefore, novel SDHIs with improved fungicidal potency are much required.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous development of the global economy and the growth of population, 1 fungicides have played an imperative role in protecting plants to ensure food quality and safety. 2,3 Among all fungicides, succinate dehydrogenase inhibitors (SDHIs), one of the best-selling categories, have attracted a lot of attention from pesticide chemists due to their excellent and broad-spectrum antifungal activities in recent years. 4−10 From 1996 to 2022, there are 24 SDHIs in the market, in which pyrazole-4-carboxamides take the largest proportion (12:24) (Figure 1A).…”
Section: ■ Introductionmentioning
confidence: 99%